Water-based modified talcum powder, polypropylene material as well as preparation method and application of water-based modified talcum powder and polypropylene material

By using water-based modified talc powder, combined with a specific amount of FEP and low odor grade water, the burnt smell problem caused by the addition of talc powder of polypropylene material is solved, and the improvement of material performance and economic benefits are achieved.

CN119798790APending Publication Date: 2025-04-11TIANJIN KINGFA NEW MATERIAL +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411988082.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing polypropylene materials produce burnt smell due to the addition of talc, which affects the odor requirements of the material.

Method used

Water-based modified talc powder is used to prepare a specific amount of FEP and low odor grade water to reduce the burnt smell caused by the addition of talc powder by polypropylene material.

Benefits of technology

It effectively reduces the burnt smell caused by the addition of talc powder of polypropylene material, improves the shrinkage, rigidity and heat resistance of the material, and reduces the amount of polypropylene resin, improving economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223043060000101
    Figure BDA0005223043060000101
  • Figure BDA0005223043060000121
    Figure BDA0005223043060000121
  • Figure BDA0005223043060000131
    Figure BDA0005223043060000131
Patent Text Reader

Abstract

The invention discloses water-based modified talcum powder, a polypropylene material and a preparation method and application of the water-based modified talcum powder, the water content of the water-based modified talcum powder is 0.4-6%, the fluorine content of the water-based modified talcum powder is 1000-15000ppm, and the odor grade of the water-based modified talcum powder is smaller than or equal to 1.5. According to the water-based modified talcum powder prepared by the invention, the burnt taste of a polypropylene material caused by the addition of the talcum powder can be reduced; when the water-based modified talcum powder is used for preparing a polypropylene material, FEP containing fluorine in the water-based modified talcum powder can be adhered to the surface of the talcum powder, so that the talcum powder is endowed with a self-lubricating property, and the shearing capacity of the talcum powder on polypropylene can be obviously weakened; and the burnt taste of the polypropylene material caused by breakage of a polypropylene molecular chain due to friction between the talcum powder and polypropylene is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and more specifically, to a water-based modified talcum powder, a polypropylene material, and a preparation method and application thereof. Background Art

[0002] With the development of the automobile industry, various OEMs, especially new energy vehicles, have put forward higher requirements for the odor of the materials used. In recent years, major domestic OEMs, injection molding plants and material plants have invested a lot of manpower and material resources in research, and have achieved good results and published a large number of patents and literature. The main material for automotive polypropylene is talcum powder filled modified polypropylene. During the processing of polypropylene, many kinds of small molecules are produced due to the addition of talcum powder, including aldehydes, ketones, acids, esters, benzenes, alkanes, olefins, amines, sulfurs, etc. These substances will produce odors, making the polypropylene material have an unpleasant burnt smell. However, as a polypropylene material for automobiles with high performance requirements, talcum powder cannot be used in order to reduce the burnt smell of polypropylene materials, because the addition of talcum powder can improve the molding shrinkage of polypropylene materials, improve the rigidity and heat resistance of polypropylene materials, and increase the surface hardness of polypropylene materials. Most importantly, the addition of talcum powder can reduce the amount of polypropylene resin and improve the economic benefits of the enterprise.

[0003] Therefore, it is of great significance to develop a water-based modified talcum powder that can reduce the burnt smell of polypropylene materials caused by the addition of talcum powder. Summary of the invention

[0004] The purpose of the present invention is to solve the problem of burnt smell of polypropylene material caused by adding talcum powder in the prior art, and to provide a water-based modified talcum powder, polypropylene material and preparation method and application thereof.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] In a first aspect, the present invention provides a water-based modified talcum powder, the water content of which is 0.4-6%, the fluorine content of which is 1000-15000 ppm, and the odor level of which is ≤1.5.

[0007] Preferably, the water content of the water-based modified talc is 0.9-5.8%, and the fluorine content is 1500-14800 ppm.

[0008] Preferably, the water-based modified talc powder comprises the following components, calculated by weight:

[0009] 100 parts of talcum powder, 0.2-2 parts of FEP, 1-6 parts of water;

[0010] The odor level of the water is ≤ level 1.5.

[0011] The water-based modified talcum powder prepared by using a specific amount of FEP and water with a specific odor level can reduce the burnt smell generated by the addition of talcum powder to the polypropylene material.

[0012] Specifically, when the water-based modified talc of the present invention is used to prepare a polypropylene material, the FEP in the water-based modified talc will adhere to the surface of the talc, giving the talc self-lubricating properties, which can significantly weaken the shearing ability of the talc on the polypropylene, and reduce the burning smell caused by the breakage of the polypropylene molecular chain due to the friction between the talc and the polypropylene.

[0013] When the water-based modified talcum powder of the present invention is used to prepare a polypropylene material, the water with a low odor level in the water-based modified talcum powder will be vaporized at high temperature to absorb and take away the low-molecular substances with odor generated in the preparation process of the polypropylene material, thereby reducing the burnt smell of the polypropylene material; moreover, the water with a low odor level will form a supercritical state between the talcum powder and the polypropylene and between the polypropylene molecules after being vaporized at high temperature, which not only reduces the burnt smell of the polypropylene material caused by the breakage of the polypropylene molecular chain due to the friction between the talcum powder and the polypropylene, but also reduces the friction between the polypropylene molecules, making it convenient for the vaporized water molecules to carry the low-molecular substances with odor to escape from between the polypropylene molecules, thereby reducing the burnt smell of the polypropylene material caused by the addition of talcum powder.

[0014] In addition, when the amount of FEP in the water-based modified talc is too small, the talc cannot be given self-lubricating properties, and the burnt smell of the polypropylene material caused by the addition of talc cannot be reduced; when the amount of FEP is too much, the excess FEP will fill in the gaps between the polypropylene molecules, preventing the vaporized water molecules from carrying odorous low-molecular substances from escaping from between the polypropylene molecules, ultimately resulting in the inability to reduce the burnt smell of the polypropylene material caused by the addition of talc.

[0015] When the odor level of water in water-based modified talcum powder is too high, it means that the water contains more small molecular substances with odor, which will be introduced into the polypropylene material, increasing the burnt smell of the polypropylene material; and the small molecular substances with odor will affect the vaporization degree of water at high temperature, making it impossible for water to absorb and take away more low molecular substances with odor generated in the preparation process of the polypropylene material, and unable to reduce the burnt smell of the polypropylene material caused by the addition of talcum powder.

[0016] In the present invention, the CAS number of FEP (Fluorinated ethylene propylene) is 25067-11-2, and it can be called fluorinated ethylene propylene copolymer, perfluoroethylene propylene copolymer, fluorinated ethylene-hexafluoropropylene copolymer or polyperfluoroethylene propylene.

[0017] In the present invention, the water content of the water-based modified talc is tested by the oven method (method A) in GB / T 15344-2020, and the test condition is 110°C.

[0018] In the present invention, the method for measuring the fluorine content of the water-based modified talc is:

[0019] Weigh the water-based modified talcum powder and put it into the crucible of the oxygen bomb tank. Put 20ml of absorption liquid at the bottom of the oxygen bomb tank. After flushing in oxygen, ignite it. After fully absorbing for 45min-60min, dilute the solution to 50ml, filter it, and use an ion chromatograph to determine the concentration of fluorine. Then, according to the concentration of fluorine in the prepared solution and the standard curve of fluorine concentration, the content of fluorine in the composition can be calculated; the standard curve is calibrated by fluoride ion solution. The absorption liquid is prepared by dissolving 0.35g of sodium carbonate and 0.65g of sodium bicarbonate in 1L of pure water.

[0020] In the present invention, the odor level test method of the water or water-based modified talcum powder is: according to the PV3900-2000 "Automotive Interior Parts Odor Detection" standard, take 20g of water sample or water-based modified talcum powder in a 1L container, adopt scheme 3 to heat at 80°C for 2h, 5 people evaluate the odor level, and 5 people conduct re-test evaluation; wherein, the odor level is divided into 1.0-6.0 points (accurate to one decimal place), corresponding to odor levels 1.0-6.0 respectively, and the test results are averaged.

[0021] More preferably, the odor level of the water is 1.0-1.5.

[0022] Water in nature is not pure water. It contains various impurities, such as dissolved gases, dissolved salts, decomposition products of organic matter, foreign pollutants, etc. The presence of these impurities causes the water to have an odor. The more impurities there are, the stronger the odor is, and the fewer impurities there are, the smaller the odor is. Water with different odor levels can be obtained by purifying water in nature. Water purification can be prepared by reverse osmosis or ion exchange. According to needs, primary reverse osmosis, secondary reverse osmosis, ion exchange or a combination of these methods can be used.

[0023] More preferably, in the water-based modified talc, the weight proportion of FEP is in the range of one or any two of 0.2, 0.4, 0.5, 0.6, 0.8, 1.0, 1.2, 1.4, 1.5, 1.6, 1.8, 2.0 parts; the weight proportion of water is in the range of one or any two of 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6 parts; the odor level of water is in the range of one or any two of 1.0, 1.1, 1.2, 1.3, 1.4, 1.5.

[0024] More preferably, the weight proportion of the FEP is 0.5-1.5 parts.

[0025] More preferably, the odor level of the water is 1.0-1.2.

[0026] More preferably, the mesh size of the talc is 1000-5000 mesh.

[0027] In a second aspect, the present invention provides a method for preparing a water-based modified talcum powder, comprising the following steps:

[0028] Take FEP dispersion containing the required amount of FEP, mix the FEP dispersion and talc powder while heating until the solvent is removed, cool it down, and then add water to mix, so as to obtain water-based modified talc powder.

[0029] Preferably, the solid content of the FEP dispersion is 20-60%.

[0030] More preferably, the solid content of the FEP dispersion is in the range of one or any two of 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%.

[0031] More preferably, the solid content of the FEP dispersion is 45-55%.

[0032] Preferably, the mixing rotation speed is 300-500 rpm.

[0033] Preferably, the heating temperature is 80-120°C.

[0034] Preferably, the cooling means that the temperature is reduced to below 50°C.

[0035] In a third aspect, the present invention provides an application of water-based modified talcum powder in polypropylene material.

[0036] In a fourth aspect, the present invention provides a polypropylene material, calculated by weight, comprising the following components:

[0037] Polypropylene 60-100 parts, water-based modified talc 4-25 parts, toughening agent 0-10 parts, odor adsorbent 0.1-2 parts, primary antioxidant 0.5-1 parts, auxiliary antioxidant 0.5-2 parts, lubricant 0.2-1 parts.

[0038] Preferably, in the polypropylene material, the weight percentage of polypropylene is 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, 100 parts or any two of the range values; the weight percentage of water-based modified talc is 3 parts, 4 parts, 5 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 26 parts or any two of the range values; the weight percentage of toughening agent is 0 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts or any two of the range values; the weight percentage of odor adsorbent is 0.1 parts, 0.3 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 10 parts or any two of the range values. 8 parts, 1.0 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2.0 parts or any two of the range values; the weight portion of the main antioxidant is 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts or any two of the range values; the weight portion of the auxiliary antioxidant is 0.5 parts, 0.6 parts, 0.8 parts, 1.0 parts, 1.1 parts, 1.3 parts, 1.5 parts, 1.7 parts, 2.0 parts or any two of the range values; the weight portion of the lubricant is 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts or any two of the range values.

[0039] Preferably, the weight proportion of the water-based modified talc is 5-20 parts.

[0040] Preferably, the weight proportion of the polypropylene is 70-90 parts.

[0041] Preferably, the polypropylene has a melt flow rate of 1-90 g / 10 min measured at 230° C. and 2.16 kg.

[0042] More preferably, the melt flow rate of the polypropylene at 230° C. and 2.16 kg is 1 g / 10 min, 2 g / 10 min, 2.5 g / 10 min, 2.6 g / 10 min, 3 g / 10 min, 4 g / 10 min, 5 g / 10 min, 10 g / 10 min, 15 g / 10 min, 20 g / 10 min, 25 g / 10 min, 26 g / 10 min, 27 g / 10 min, The range value of one or any two of 28g / 10min, 29g / 10min, 30g / 10min, 35g / 10min, 40g / 10min, 45g / 10min, 50g / 10min, 55g / 10min, 60g / 10min, 65g / 10min, 70g / 10min, 75g / 10min, 80g / 10min, 85g / 10min, and 90g / 10min.

[0043] More preferably, the melt flow rate of the polypropylene measured at 230° C. and 2.16 kg is 2-60 g / 10 min, specifically 2.5-60 g / 10 min.

[0044] In the present invention, the melt flow rate (melt mass flow rate) of the polypropylene can be measured according to GB / T-3682-2000.

[0045] Preferably, the toughening agent is at least one of POE, PE, EPDM, SEBS, SBS, EVA, EEA, EBA, and EMA.

[0046] More preferably, the melt flow rate of the POE measured at 230° C. and 2.16 kg is 1-30 g / 10 min.

[0047] More preferably, the melt flow rate of the POE at 230°C and 2.16kg is in the range of one or any two of 1g / 10min, 1.2g / 10min, 1.5g / 10min, 2g / 10min, 5g / 10min, 10g / 10min, 11g / 10min, 12g / 10min, 13g / 10min, 14g / 10min, 15g / 10min, 16g / 10min, 17g / 10min, 18g / 10min, 19g / 10min, 20g / 10min, 25g / 10min, and 30g / 10min.

[0048] More preferably, the melt flow rate of the POE measured at 230° C. and 2.16 kg is 5-18 g / 10 min.

[0049] In the present invention, the melt flow rate (melt mass flow rate) of the toughening agent (including POE, etc.) can be measured according to GB / T-3682-2000.

[0050] In the present invention, the toughening agent is used to improve the toughness and low-temperature toughness of the polypropylene material. Although it will emit a burnt smell after being subjected to shear force, which enhances the burnt smell of the polypropylene material, the toughening effect of the toughening agent is required by most automotive interior and exterior materials, so the toughening agent is often a necessary component to be added. The selection of POE with a specific melt flow rate can form a sufficient "island" structure in the polypropylene material, reduce the shear force on POE during the preparation of the polypropylene material, reduce the burnt smell of POE, and thus reduce the burnt smell of the polypropylene material.

[0051] Preferably, the odor adsorbent is at least one of porous substance A and porous substance B, the porous substance A is at least one of zeolite, diatomaceous earth, and molecular sieve with an average pore size of 6-10nm, and the porous substance B is at least one of zeolite, diatomaceous earth, and molecular sieve with an average pore size of >10nm and ≤15nm.

[0052] More preferably, the odor adsorbent is porous substance A and porous substance B in a mass ratio of 1:(0.3-3).

[0053] More preferably, the particle size of the porous substance A is 10-15 μm, and the particle size of the porous substance B is greater than 15 μm and less than or equal to 25 μm.

[0054] The average pore size test method of the odor adsorbent (porous material A and porous material B) is: using nitrogen as the adsorbent, using TriStarⅡplus 3030, and testing the average pore size of porous material A and / or porous material B in accordance with the national standard GB / T 21650.2-2008.

[0055] The average particle size test method of the odor adsorbent (porous substance A and porous substance B) is as follows: the average particle size of porous substance A and / or porous substance B is measured in accordance with the national standard GB / T19077-2024.

[0056] In the present invention, the odor adsorbent can be heated at 150-250° C. for ≥60 min before use, and then placed in a sealed container to cool to room temperature before use.

[0057] Preferably, the primary antioxidant is at least one of a hindered phenol antioxidant, a hindered phenol and hydrazide dual structure antioxidant, and an amine antioxidant.

[0058] In the present invention, the hindered phenol and hydrazide dual structure antioxidant refers to an antioxidant having a hindered phenol structure and a hydrazide structure.

[0059] Preferably, the auxiliary antioxidant is at least one of a phosphite antioxidant and a thioether antioxidant.

[0060] Preferably, the lubricant is at least one of a stearic acid lubricant and an amide lubricant.

[0061] In a fifth aspect, the present invention provides a method for preparing a polypropylene material, comprising the following steps:

[0062] S1. Mixing the other components except the water-based modified talc to obtain a mixture;

[0063] S2. Mix the water-based modified talcum powder and the mixture obtained in step S1, extrude and granulate to obtain a polypropylene material.

[0064] Preferably, the granulation further comprises at least one of washing and baking.

[0065] More preferably, the baking temperature is 80-120° C. and the baking time is 6-24 h.

[0066] Preferably, a twin-screw extruder is used during the extrusion.

[0067] More preferably, the aspect ratio of the twin-screw extruder is (44-56):1.

[0068] More preferably, the temperature of the first zone of the twin-screw extruder is 80-120°C, the temperature of the second zone of the body is 100-140°C, the temperature of the third zone of the body is 140-180°C, the temperature of the fourth zone of the body is 150-190°C, the temperature of the fifth zone of the body is 160-200°C, and the temperature starting from the sixth zone is 180-220°C.

[0069] More preferably, the vacuum degree of the vacuum hole of the twin-screw extruder is ≤-0.08MPa.

[0070] In a sixth aspect, the present invention provides an application of a polypropylene material in an automobile.

[0071] Compared with the prior art, the present invention has the following beneficial effects:

[0072] The water-based modified talcum powder prepared by using a specific amount of FEP and water with a specific odor level can reduce the burnt smell generated by the addition of talcum powder to the polypropylene material.

[0073] Specifically, when the water-based modified talc of the present invention is used to prepare a polypropylene material, the FEP in the water-based modified talc will adhere to the surface of the talc, giving the talc self-lubricating properties, which can significantly weaken the shearing ability of the talc on the polypropylene, and reduce the burning smell caused by the breakage of the polypropylene molecular chain due to the friction between the talc and the polypropylene.

[0074] When the water-based modified talcum powder of the present invention is used to prepare a polypropylene material, the water with a low odor level in the water-based modified talcum powder will be vaporized at high temperature to absorb and take away the low-molecular substances with odor generated in the preparation process of the polypropylene material, thereby reducing the burnt smell of the polypropylene material; moreover, the water with a low odor level will form a supercritical state between the talcum powder and the polypropylene and between the polypropylene molecules after being vaporized at high temperature, which not only reduces the burnt smell of the polypropylene material caused by the breakage of the polypropylene molecular chain due to the friction between the talcum powder and the polypropylene, but also reduces the friction between the polypropylene molecules, making it convenient for the vaporized water molecules to carry the low-molecular substances with odor to escape from between the polypropylene molecules, thereby reducing the burnt smell of the polypropylene material caused by the addition of talcum powder.

[0075] In addition, when the amount of FEP in the water-based modified talc is too small, the talc cannot be given self-lubricating properties, and the burnt smell of the polypropylene material caused by the addition of talc cannot be reduced; when the amount of FEP is too much, the excess FEP will fill in the gaps between the polypropylene molecules, preventing the vaporized water molecules from carrying odorous low-molecular substances from escaping from between the polypropylene molecules, ultimately resulting in the inability to reduce the burnt smell of the polypropylene material caused by the addition of talc.

[0076] When the odor level of water in water-based modified talcum powder is too high, it means that the water contains more small molecular substances with odor, which will be introduced into the polypropylene material, increasing the burnt smell of the polypropylene material; and the small molecular substances with odor will affect the vaporization degree of water at high temperature, making it impossible for water to absorb and take away more low molecular substances with odor generated in the preparation process of the polypropylene material, and unable to reduce the burnt smell of the polypropylene material caused by the addition of talcum powder. DETAILED DESCRIPTION

[0077] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific preparation examples.

[0078] The experimental methods without specific conditions in the following preparation examples, comparative preparation examples, embodiments and comparative examples are generally carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets.

[0079] In each preparation example and comparative preparation example of the present invention, the use of reagents is as follows:

[0080] FEP dispersion: FC-D-1, with a solid content of about 50%, produced by Fine Fluoro Technology; when preparing water-based modified talcum powder, the FEP dispersion can be weighed according to the actual amount of FEP required;

[0081] Talc: TYT-777A, Tianyuan Chemical, 3000 mesh, no surface treatment;

[0082] Water 1: Water, odor level 1.0, obtained by selecting tap water after secondary reverse osmosis;

[0083] Water 2: Water, odor level 1.2, can be obtained by selecting tap water after first-level reverse osmosis;

[0084] Water 3: Water, odor level 1.5, can be obtained by selecting tap water;

[0085] Water 4: Water, odor level 2.0, can be obtained by selecting industrial water;

[0086] The preparation method of water-based talcum powder is as follows: add talcum powder into a high-speed heating mixer, stir at a speed of 400 rpm and a temperature of 100°C, gradually add FEP dispersion liquid to mix evenly, cool to below 50°C after the FEP solvent evaporates, spray water while stirring to mix evenly, discharge and seal and package to obtain water-based modified talcum powder.

[0087] Polypropylene 1: PP Y26, melt flow rate at 230°C, 2.16 kg is 26 g / 10 min, Zhenhai Refining and Chemical;

[0088] Polypropylene 2: PP BX3900, melt flow rate 60 g / 10 min at 230 °C and 2.16 kg, SK, Korea;

[0089] Polypropylene 3: PP T30S, melt flow rate at 230°C, 2.16 kg is 2.6 g / 10 min, Lanzhou Petrochemical;

[0090] Polypropylene 4: PP BX3920, melt flow rate 90 g / 10 min at 230 °C and 2.16 kg, SK, Korea;

[0091] Polypropylene 5: PP T1701, melt flow rate at 230°C, 2.16kg is 1.0 g / 10 min, Yanshan Petrochemical;

[0092] Toughener 1: POE, ENGAGE 8137, DOW Chemical (Dow, USA), melt flow rate at 190°C, 2.16 kg is 13 g / 10 min;

[0093] Toughener 2: POE, ENGAGE 8411, DOW Chemical (Dow, USA), melt flow rate at 190°C, 2.16 kg is 18 g / 10 min;

[0094] Toughener 3: POE, ENGAGE 8200, DOW Chemical (Dow, USA), melt flow rate at 190°C, 2.16 kg is 5 g / 10 min;

[0095] Toughener 4: POE, ENGAGE 8401, DOW Chemical (Dow, USA), melt flow rate at 190°C, 2.16 kg is 30 g / 10 min;

[0096] Toughener 5: POE, ENGAGE 7467, DOW Chemical (Dow, USA), melt flow rate at 190°C, 2.16 kg is 1.2 g / 10 min;

[0097] Odor adsorbent: porous substance A and porous substance B in a mass ratio of 1:1, wherein the porous substance A is a molecular sieve with an average pore size of 8 nm and an average particle size of 11 μm (Tianjin Guolong, MS10E), and the porous substance B is diatomaceous earth with an average pore size of 12 nm and an average particle size of 20 μm (Zhejiang Erneng, Y-G500); the odor adsorbent is heated at 200°C for 60 min before use, and then placed in a sealed container to cool to room temperature before use;

[0098] Primary antioxidant: antioxidant 1010, commercially available;

[0099] Secondary antioxidant: antioxidant 168, commercially available;

[0100] Lubricant: Zinc stearate, commercially available.

[0101] Among the above reagents, the melt flow rate (melt mass flow rate) of polypropylene and toughening agent can be measured according to GB / T-3682-2000.

[0102] Among the above reagents, the average pore size test method of the odor adsorbent (porous substance A and porous substance B) is: using nitrogen as the adsorbent, using TriStarⅡplus 3030, and testing the average pore size of porous substance A and / or porous substance B in accordance with the national standard GB / T21650.2-2008.

[0103] In the above reagents, the average particle size test method of the odor adsorbent (porous substance A and porous substance B) is: measuring the average particle size of porous substance A and / or porous substance B according to the national standard GB / T 19077-2024.

[0104] Preparation Examples 1-7 and Comparative Preparation Examples 1-5

[0105] Preparation Examples 1-7 and Comparative Preparation Examples 1-5 provide different water-based modified talc powders, the only difference between them being the types and amounts of the components. Calculated by weight, Preparation Examples 1-7 and Comparative Preparation Examples 1-5 respectively include the components shown in Table 1;

[0106] The preparation methods of the water-based modified talc powders of Preparation Examples 1-7 and Comparative Preparation Examples 1-5 include the following steps:

[0107] First, add talcum powder into a high-speed heating mixer, then take FEP dispersion containing the required amount of FEP, add the FEP dispersion into the talcum powder while heating at 400 rpm and 100°C, and mix until the solvent is removed, cool to 40°C, continue to stir and add water at 400 rpm to obtain water-based modified talcum powder;

[0108] Table 1 Weight fractions of each component in the water-based modified talc powder of Preparation Examples 1-7 and Comparative Preparation Examples 1-5

[0109]

[0110] Note: When preparing water-based modified talc, the FEP dispersion can be weighed according to the actual amount of FEP required. For example, when preparing water-based modified talc in Example 1, 1 part of FEP is required, and 2 parts of FEP dispersion with a solid content of about 50% can be weighed to replace it;

[0111] In the present invention, the water content of the water-based modified talc is tested by the oven method (method A) in GB / T 15344-2020, and the test condition is 110°C.

[0112] In the present invention, the method for measuring the fluorine content of the water-based modified talc is:

[0113] Weigh water-based modified talcum powder (about 0.5g), put it into the crucible of the oxygen bomb tank, and put 20ml of absorption liquid at the bottom of the oxygen bomb tank. After flushing in oxygen, ignite it. After fully absorbing for 45min-60min, dilute the solution to 50ml, filter it, and use Shenghan CIC-D160 model ion chromatograph to determine the concentration of fluorine element. Then, according to the concentration of fluorine element in the prepared solution and the fluorine element concentration standard curve, the content of fluorine element in the composition can be calculated; the standard curve is calibrated by fluoride ion solution. The absorption liquid is prepared by dissolving 0.35g of sodium carbonate and 0.65g of sodium bicarbonate in 1L of pure water.

[0114] In the present invention, the odor level test method of the water or water-based modified talcum powder is: according to the PV3900-2000 "Automotive Interior Parts Odor Detection" standard, take 20g of water sample or water-based modified talcum powder in a 1L container, adopt scheme 3 to heat at 80°C for 2h, 5 people evaluate the odor level, and 5 people conduct re-test evaluation; wherein, the odor level is divided into 1.0-6.0 points (accurate to one decimal place), corresponding to odor levels 1.0-6.0 respectively, and the test results are averaged.

[0115] Examples 1-20 and Comparative Examples 1-5

[0116] Examples 1-20 and Comparative Examples 1-5 provide different polypropylene materials, and the only difference between them is that the types and amounts of the components are different. Calculated by weight, Examples 1-20 and Comparative Examples 1-5 respectively include the components shown in Table 2;

[0117] The preparation method of the polypropylene material of Examples 1-20 and Comparative Examples 1-6 comprises the following steps:

[0118] S1. Mixing the other components except the water-based modified talc to obtain a mixture;

[0119] S2. Add the mixture obtained in step S1 to the main feed port of the twin-screw extruder, add water-based modified talc to the side feed port of the twin-screw extruder (located in the fifth zone of the fuselage) and mix, extrude, granulate, wash, and bake at 120 ° C for 16h to obtain a polypropylene material;

[0120] The aspect ratio of the twin-screw extruder is 48:1, the temperature of the first zone of the twin-screw extruder is 80°C, the temperature of the second zone of the twin-screw extruder is 120°C, the temperature of the third zone of the twin-screw extruder is 160°C, the temperature of the fourth zone of the twin-screw extruder is 170°C, the temperature of the fifth zone of the twin-screw extruder is 180°C, the temperature of the sixth zone of the twin-screw extruder is 200°C, the temperature of the seventh zone of the twin-screw extruder is 200°C, the temperature of the eighth zone of the twin-screw extruder is 200°C, the temperature of the tenth zone of the twin-screw extruder is 200°C, the temperature of the eleventh zone of the twin-screw extruder is 200°C, and the vacuum degree of the vacuum hole of the twin-screw extruder is -0.08MPa;

[0121] Table 2 Weight parts of each component in the polypropylene material of Examples 1-20 and Comparative Examples 1-5

[0122]

[0123]

[0124]

[0125] Performance Testing

[0126] The polypropylene materials of each embodiment and comparative example were tested for burnt smell performance:

[0127] (1) The pellets of the polypropylene material of each embodiment and comparative example were tested for burnt odor performance:

[0128] According to the PV3900-2000 "Odor Detection of Automotive Interior Parts" standard, 20 g of the polypropylene material (granules) of each embodiment or comparative example was taken in a 1 L container, and heated at 80°C for 2 h using Scheme 3. Five people evaluated the odor level, and five people conducted retest evaluation; the odor level was divided into 1.0-6.0 points (accurate to one decimal place), the larger the score, the more unpleasant the smell, and the test results were averaged; when the odor level was ≤3.0 points, it indicated that there was no burnt smell; when the odor level was 3.0-3.5 (inclusive), it indicated that there was a slight burnt smell; when the odor level was 3.5 (not included)-4.0 (inclusive), it indicated that there was a heavier burnt smell; when the odor level was 4.0 (not included)-6.0 points, it indicated that there was a serious burnt smell;

[0129] (2) The polypropylene sheet materials of each embodiment and comparative example were tested for burnt odor performance:

[0130] A. Take the polypropylene material (granules) of each embodiment or comparative example, heat it at 220°C to make a sheet of 100mm×100mm×2mm (length×width×height), place the sheet in a 1L container, and heat it at 80°C for 2h using Scheme 3. Five people evaluate the odor level, and five people conduct retest evaluation; wherein the odor level is divided into 1.0-6.0 points (accurate to one decimal place), the larger the score, the more unpleasant the smell, and the test results are averaged; when the odor level is ≤3.0 points, it means there is no burnt smell; when the odor level is 3.0-3.5 (inclusive), it means there is a slight burnt smell; when the odor level is 3.5 (not included)-4.0 (inclusive), it means there is a heavier burnt smell; when the odor level is 4.0 (not included)-6.0, it means there is a serious burnt smell;

[0131] The experimental results are shown in the following table:

[0132] Table 3 Burnt smell performance test results of polypropylene materials in various embodiments and comparative examples

[0133]

[0134]

[0135] As can be seen from Table 3, the water-based modified talcum powder prepared by the present invention using a specific amount of FEP and water with a specific odor level can reduce the burnt smell generated by the addition of talcum powder to the polypropylene material.

[0136] Specifically, when the water-based modified talc of the present invention is used to prepare a polypropylene material, the FEP in the water-based modified talc will adhere to the surface of the talc, giving the talc self-lubricating properties, which can significantly weaken the shearing ability of the talc on the polypropylene, and reduce the burning smell caused by the breakage of the polypropylene molecular chain due to the friction between the talc and the polypropylene.

[0137] When the water-based modified talcum powder of the present invention is used to prepare a polypropylene material, the water with a low odor level in the water-based modified talcum powder will be vaporized at high temperature to absorb and take away the low-molecular substances with odor generated in the preparation process of the polypropylene material, thereby reducing the burnt smell of the polypropylene material; moreover, the water with a low odor level will form a supercritical state between the talcum powder and the polypropylene and between the polypropylene molecules after being vaporized at high temperature, which not only reduces the burnt smell of the polypropylene material caused by the breakage of the polypropylene molecular chain due to the friction between the talcum powder and the polypropylene, but also reduces the friction between the polypropylene molecules, making it convenient for the vaporized water molecules to carry the low-molecular substances with odor to escape from between the polypropylene molecules, thereby reducing the burnt smell of the polypropylene material caused by the addition of talcum powder.

[0138] In addition, it can be seen from Examples 1-3 and Comparative Examples 1-2 that when the amount of FEP in the water-based modified talc is too small, the talc cannot be given self-lubricating properties, and the burnt smell of the polypropylene material caused by the addition of talc cannot be reduced; when the amount of FEP is too much, the excess FEP will fill in the polypropylene molecules, preventing the vaporized water molecules from carrying odorous low-molecular substances from escaping from between the polypropylene molecules, ultimately resulting in the inability to reduce the burnt smell of the polypropylene material caused by the addition of talc.

[0139] It can be seen from Examples 1, 4-5 and Comparative Example 3 that when the odor level of water in the water-based modified talcum powder is too high, it means that the water contains more small molecular substances with odor, and these substances will be introduced into the polypropylene material, increasing the burnt smell of the polypropylene material; and the small molecular substances with odor will affect the gasification degree of water at high temperature, so that the water cannot absorb and take away more low molecular substances with odor generated in the preparation process of the polypropylene material, and cannot reduce the burnt smell of the polypropylene material caused by the addition of talcum powder.

[0140] It can be seen from Examples 1 and 10-13 that, in the present invention, the selection of POE with a specific melt flow rate can form a sufficient "island" structure in the polypropylene material, reduce the shear force exerted on POE during the preparation of the polypropylene material, reduce the burnt smell of POE, and thus reduce the burnt smell of the polypropylene material.

[0141] Finally, it should be noted that the above preparation examples are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the preferred preparation examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A water-based modified talcum powder, characterized in that: Its water content is 0.4-6%, its fluorine content is 1000-15000ppm, and its odor level is ≤1.

5.

2. The water-based modified talcum powder according to claim 1, characterized in that: The water-based modified talcum powder comprises the following components, calculated by weight: 100 parts of talcum powder, 0.2-2 parts of FEP, 1-6 parts of water; The odor level of the water is ≤ level 1.

5.

3. The water-based modified talcum powder as claimed in claim 2, characterized in that: Include at least one of the following (1)-(2): (1) The odor level of the water is 1.0-1.5; (2) The weight proportion of the FEP is 0.5-1.5 parts.

4. A method for preparing the water-based modified talc according to any one of claims 1 to 3, characterized in that: The steps include: Take FEP dispersion containing the required amount of FEP, mix the FEP dispersion and talc powder while heating until the solvent is removed, cool it down, and then add water to mix, so as to obtain water-based modified talc powder.

5. Use of the water-based modified talc according to any one of claims 1 to 3 in polypropylene materials.

6. A polypropylene material, characterized in that: Calculated by weight, it includes the following components: 60-100 parts of polypropylene, 4-25 parts of the water-based modified talc as claimed in any one of claims 1-3, 0-10 parts of a toughening agent, 0.1-2 parts of an odor absorbent, 0.5-1 parts of a primary antioxidant, 0.5-2 parts of a secondary antioxidant, and 0.2-1 parts of a lubricant.

7. The polypropylene material according to claim 6, characterized in that: Including at least one of the following (1)-(8): (1) The weight proportion of the water-based modified talc is 5-20 parts; (2) The weight proportion of the polypropylene is 70-90 parts; (3) The melt flow rate of the polypropylene measured at 230° C. and 2.16 kg is 1-90 g / 10 min; (4) The toughening agent is at least one of POE, PE, EPDM, SEBS, SBS, EVA, EEA, EBA, and EMA; (5) The odor adsorbent is at least one of porous material A and porous material B, wherein the porous material A is at least one of zeolite, diatomaceous earth, and molecular sieve with an average pore size of 6-10 nm, and the porous material B is at least one of zeolite, diatomaceous earth, and molecular sieve with an average pore size of >10 nm and ≤15 nm; (6) The primary antioxidant is at least one of a hindered phenol antioxidant, a hindered phenol and hydrazide dual structure antioxidant, and an amine antioxidant; (7) The auxiliary antioxidant is at least one of a phosphite antioxidant and a thioether antioxidant; (8) The lubricant is at least one of a stearic acid lubricant and an amide lubricant.

8. The polypropylene material according to claim 7, characterized in that: Include at least one of the following (1)-(2): (1) The polypropylene has a melt flow rate of 2-60 g / 10 min measured at 230° C. and 2.16 kg; (2) The melt flow rate of the POE measured at 230° C. and 2.16 kg is 1-30 g / 10 min.

9. A method for preparing the polypropylene material according to any one of claims 6 to 8, characterized in that: The steps include: S1. Mixing the other components except the water-based modified talc to obtain a mixture; S2. Mix the water-based modified talcum powder and the mixture obtained in step S1, extrude and granulate to obtain a polypropylene material.

10. Use of the polypropylene material according to any one of claims 6 to 8 in automobiles.

Citation Information

Cited By

  • Water-based modified talcum powder, and polypropylene material, and preparation method therefor and use thereof

    WO2026145636A1